On the Tradeoff between Hardware Protection and Optimization Success: A Case Study in Onboard Evolutionary Robotics for Autonomous Parallel Parking - Wahby, Mostafa; Hamann, Heiko (Applications of Evolutionary Computation (EvoApplications 2015))

Flora Robotica - Mixed Societies of Symbiotic Robot-Plant Bio-Hybrids - Hamann, Heiko; Wahby, Mostafa; Schmickl, Thomas; Zahadat, Payam; Hofstadler, Daniel; Stoy, Kasper; Risi, Sebastian; Faina, Andres; Veenstra, Frank; Kernbach, Serge; Kuksin, Igor; Kernbach, Olga; et al. (Proceedings of the 2015 IEEE Symposium on Artificial Life (IEEE ALIFE'15))
Besides the life-as-it-could-be driver of artificial life research there is also the concept of extending natural life by creating hybrids or mixed societies that are built from natural and artificial components. In this paper we motivate and present the research program of the project flora robotica. Our objective is to develop and to investigate closely linked symbiotic relationships between robots and natural plants and to explore the potentials of a plant-robot society able to produce architectural artifacts and living spaces. These robot-plant bio-hybrids create synergies that allow for new functions of plants and robots. They also create novel design opportunities for an architecture that fuses the design and construction phase. The bio-hybrid is an example of mixed societies between 'hard' artificial and 'wet' natural life, which enables an interaction between natural and artificial ecologies. They form an embodied, self-organizing, and distributed cognitive system which is supposed to grow and develop over long periods of time resulting in the creation of meaningful architectural structures. A key idea is to assign equal roles to robots and plants in order to create a highly integrated, symbiotic system. Besides the gain of knowledge, this project has the objective to create a bio-hybrid system with a defined function and application -- growing architectural artifacts.

Lessons from Speciation Dynamics: How to Generate Selective Pressure Towards Diversity - Hamann, Heiko (Artificial Life)
Recent approaches in evolutionary robotics (ER) propose to generate behavioral diversity in order to evolve desired behaviors more easily. These approaches require the definition of a behavioral distance, which often includes task-specific features and hence a priori knowledge. Alternative methods, which do not explicitly force selective pressure towards diversity (SPTD) but still generate it, are known from the field of artificial life, such as in artificial ecologies (AEs). In this study, we investigate how SPTD is generated without task-specific behavioral features or other forms of a priori knowledge and detect how methods of generating SPTD can be transferred from the domain of AE to ER. A promising finding is that in both types of systems, in systems from ER that generate behavioral diversity and also in the investigated speciation model, selective pressure is generated towards unpopulated regions of search space. In a simple case study we investigate the practical implications of these findings and point to options for transferring the idea of self-organizing SPTD in AEs to the domain of ER.

Revisiting BEECLUST: Aggregation of Swarm Robots with Adaptiveness to Different Light Settings - Wahby, Mostafa; Weinhold, Alexander; Hamann, Heiko (Proceedings of the 9th EAI International Conference on Bio-inspired Information and Communications Technologies (formerly BIONETICS))
Aggregation is a crucial task in swarm robotics to ensure cooperation. We investigate the task of aggregation on an area specified indirectly by certain environmental features, here it is a light distribution. We extend the original BEECLUST algorithm, that implements an aggregation behavior, to an adaptive variant that automatically adapts to any light conditions. We compare these two control algorithms in a number of swarm robot experiments with different light conditions. The improved, adaptive variant is found to be significantly better in the tested setup.

Evolution of Controllers for Robot-Plant Bio-Hybdrids: A Simple Case Study Using a Model of Plant Growth and Motion - Wahby, Mostafa; Divband Soorati, Mohammad; von Mammen, Sebastian; Hamann, Heiko (Proceedings. 25. Computational Intelligence Workshop)

The Effect of Fitness Function Design on Performance in Evolutionary Robotics: The Influence of a Priori Knowledge - Hamann, Heiko; Divband Soorati, Mohammad (Proceedings of the Genetic and Evolutionary Computation Conference (GECCO 2015))
Fitness function design is known to be a critical feature of the evolutionary-robotics approach. Potentially, the complexity of evolving a successful controller for a given task can be reduced by integrating a priori knowledge into the fitness function which complicates the comparability of studies in evolutionary robotics. Still, there are only few publications that study the actual effects of different fitness functions on the robot's performance. In this paper, we follow the fitness function classification of Nelson et al. (2009) and investigate a selection of four classes of fitness functions that require different degrees of a priori knowledge. The robot controllers are evolved in simulation using NEAT and we investigate different tasks including obstacle avoidance and (periodic) goal homing. The best evolved controllers were then post-evaluated by examining their potential for adaptation, determining their convergence rates, and using cross-comparisons based on the different fitness function classes. The results confirm that the integration of more a priori knowledge can simplify a task and show that more attention should be paid to fitness function classes when comparing different studies.

Evolving Collective Behaviors With Diverse But Predictable Sensor States - Hamann, Heiko; Schmickl, Thomas; Zahadat, Payam (13th European Conference on Artificial Life (ECAL 2015))

Probabilistic Modeling of Swarming Systems - Hamann, Heiko; Correll, Nikolaus; Kacprzyk, Janusz; Pedrycz, Witold (Springer Handbook of Computational Intelligence)

Dependability in Swarm Robotics: Error Detection and Correction - Ding, Hongli; Hamann, Heiko (First International Symposium on Swarm Behavior and Bio-Inspired Robotics (SWARM 2015))

Potential of Heterogeneity in Collective Behaviors: A Case Study on Heterogeneous Swarms - Hamann, Heiko; Schmickl, Thomas; Kengyel, Daniela; Zahadat, Payam; Radspieler, Gerald; Wotawa, Franz (Principles and Practice of Multi-Agent Systems (PRIMA 2015))

Time-variant feedback processes in collective decision-making systems: influence and effect of dynamic neighborhood sizes - Valentini, Gabriele; Hamann, Heiko (Swarm Intelligence)

Efficient Decision-Making in a Self-Organizing Robot Swarm: On the Speed Versus Accuracy Trade-Off - Dorigo, Marco; Hamann, Heiko; Valentini, Gabriele (Proceedings of the 14th Int. Conf. on Autonomous Agents and Multiagent Systems (AAMAS 2015))

Self-organized collective decisions in a robot swarm - Dorigo, Marco; Hamann, Heiko; Valentini, Gabriele (AAAI-15 Video Proceedings)

Optimized method in sizing of Flapping Wing - Kaveh, Mahdi; Pourmohammad, Javad; Hassanalian, Mostafa; Nili Ahmadabadi, Mahdi; Otroshi, Mortaza

Market-Specific Service Compositions: Specification and Matching - Arifulina, Svetlana; Platenius, Marie Christin; Mohr, Felix; Engels, Gregor; Schäfer, Wilhelm (Proceedings of the IEEE 11th World Congress on Services (SERVICES), Visionary Track: Service Composition for the Future Internet)
The Collaborative Research Centre "On-The-Fly Computing" works on foundations and principles for the vision of the Future Internet. It proposes the paradigm of On-The-Fly Computing, which tackles emerging worldwide service markets. In these markets, service providers trade software, platform, and infrastructure as a service. Service requesters state requirements on services. To satisfy these requirements, the new role of brokers, who are (human) actors building service compositions on the fly, is introduced. Brokers have to specify service compositions formally and comprehensively using a domain-specific language (DSL), and to use service matching for the discovery of the constituent services available in the market. The broker's choice of the DSL and matching approaches influences her success of building compositions as distinctive properties of different service markets play a significant role. In this paper, we propose a new approach of engineering a situation-specific DSL by customizing a comprehensive, modular DSL and its matching for given service market properties. This enables the broker to create market-specific composition specifications and to perform market-specific service matching. As a result, the broker builds service compositions satisfying the requester's requirements more accurately. We evaluated the presented concepts using case studies in service markets for tourism and university management.

Changes in dietary intake during puberty and their determinants: results from the GINIplus birth cohort study - Harris, Carla; Flexeder, Claudia; Thiering, Elisabeth; Buyken, Anette; Berdel, Dietrich; Koletzko, Sibylle; Bauer, Carl-Peter; Brüske, Irene; Koletzko, Berthold; Standl, Marie (BMC Public Health)
Background Understanding changes in dietary intake during puberty could aid the mapping of dietary interventions for primary prevention. The present study describes dietary changes from childhood to adolescence, and their associations with parental education, family income, child education, body mass index (BMI), pubertal onset and screen-time sedentary behaviour. Methods Dietary data (n = 1232) were obtained from food frequency questionnaires at the 10- and 15-year follow-ups of the GINIplus birth cohort study. Intakes of 17 food groups, macronutrients and antioxidant vitamins, were described by a) paired Wilcoxon rank sum tests, comparing average intakes at each time-point, and b) Cohen’s kappa “tracking” coefficients, measuring stability of intakes (maintenance of relative tertile positions across time). Further, associations of changes (tertile position increase or decrease vs. tracking) with parental education, family income, child education, pubertal onset, BMI, and screen-time, were assessed by logistic regression and multinomial logistic regression models stratified by baseline intake tertile. Results Both sexes increased average intakes of water and decreased starchy vegetables, margarine and dairy. Females decreased meat and retinol intakes and increased vegetables, grains, oils and tea. Males decreased fruit and carbohydrates and increased average intakes of meat, caloric drinks, water, protein, fat, polyunsaturated fatty acids (PUFAs), vitamin C and alpha-tocopherol. Both sexes presented mainly “fair” tracking levels [κw = 0.21–0.40]. Females with high (vs. low) parental education were more likely to increase their nut intake [OR = 3.8; 95 % CI = (1.7;8.8)], and less likely to decrease vitamin C intakes [0.2 (0.1;0.5)], while males were less likely to increase egg consumption [0.2 (0.1;0.5)] and n3 PUFAs [0.2 (0.1;0.5)]. Females with a higher (vs. low) family income were more likely to maintain medium wholegrain intakes [0.2 (0.1;0.7) for decrease vs. tracking, and 0.1 (0.0;0.5) for increase vs. tracking], and were less likely to decrease vitamin C intakes [0.2 (0.1;0.6)]. Males with high education were less likely to increase sugar-sweetened foods [0.1 (0.1;0.4)]. Finally, BMI in females was negatively associated with decreasing protein intakes [0.7 (0.6;0.9)]. In males BMI was positively associated with increasing margarine [1.4 (1.1;1.6)] and vitamin C intakes [1.4 (1.1;1.6)], and negatively associated with increasing n3 PUFA. Conclusions Average dietary intakes changed significantly, despite fair tracking levels, suggesting the presence of trends in dietary behaviour during puberty. Family income and parental education predominantly influenced intake changes. Our results support the rationale for dietary interventions targeting children, and suggest that sex-specific subpopulations, e.g. low socio-economic status, should be considered for added impact.
Keywords: Puberty; Dietary intake; Dietary changes; Tracking; Determinants; Epidemiology

Lernpotential durch Lehrerkooperation. Vorstellung eines Analyseansatzes zur Erfassung erfahrungsbezogener Lerngelegenheiten. - Bloh, Thiemo; Bloh, Bea; van Ophuysen, Stefanie (Empirische Pädagogik)

Load Balancing for Range Queries in a Dimension Invariant Peer-to-Peer Network - Rojahn, Tobias

Playing the Lottery or Dressing Up? A Model of Firm-Level Heterogeneity and the Decision to Export - Gries, Thomas; Naudé, Wim; Bilkic, Natascha (The Quarterly Review of Economics and Finance)

Changes of China’s agri-food exports to Germany caused by its accession to WTO and the 2008 financial crisis - Gries, Thomas; Feng, Yuanhua; Guo, Zhichao (China Agricultural Economic Review)